A New Method of Bio-Catalytic Surface Modification for Microbial Desalination Cell - Ummy Mardiana; Christophe Innocent; Marc Cretin; Buchari Buchari (International Journal of Renewable Energy Development, 2021)
A microbial desalination cell (MDC) built on a modified surface has been studied for seawater desalination. The goal of this study is to provide and develop a seawater desalination system that does not require energy support by applying a modification of the anode as an electron acceptor. The different potential charges that occur between anode and cathode can serve as the driving force for electrodialysis of seawater, resulting in its desalination. Yeast has been applied as a biocatalyst and neutral red has been chosen as a redox mediator to facilitate the electron transport originating from the bioactivity of cells. Several types of surface modification have been conducted, i.e., biocatalyst-mediator immobilisation and electropolymerisation of neutral red at the anode surface. The optimisation of each device has been characterised by cyclic voltammetry and chronoamperometry. It has also been observed in a microbial fuel cell (MFC), prior to being functioned in the MDC. The concentrations of salt ion migration have been determined by ion exchange chromatography. This study found that the best configuration of a modified surface was obtained from carbon felt coated by polyneutral red film (CF/PNR); this generated the maximum value of all tested parameters: 42.2% of current efficiency; 27.11% of bio-devices efficiency; 92.5 mA m-2 of current density; and 61% of NaCl transport. Moreover, the modified surface could be a promising method for improving anode performance.